1987
DOI: 10.1002/j.1537-2197.1987.tb08677.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Mycorrhizal Ecology of Prairie Dropseed, Sporobolus Heterolepis (Poaceae)

Abstract: Vesicular‐arbuscular mycorrhizal (VAM) fungal colonization of prairie dropseed and rhizosphere spore abundance were sampled seasonally at two sites in Illinois. At Goose Lake Prairie (GLP), Gaussian ordination of 49 vegetation stands, using plant cover data for 40 species, assigned stands x‐vector values and ordered them along a soil moisture‐nutrient gradient. Prairie dropseed cover data plotted over ordered stands yielded a significant Gaussian curve across a relatively narrow gradient segment. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
3
4
1
Order By: Relevance
“…AM colonization of S. wrightii continued at a higher level in the summer ( July) at two sampling sites ( UP and UI), but then declined to the lowest levels in fall (September) when big sacaton shifted from vegetative growth to reproduction, and in December when hosts were dormant, or approaching dormancy. This pattern of change in fungal colonization is similar to that reported by Ebbers et al (1987) in their study of S. heterolepsis. Bentivenga & Hetrick (1992) found total colonization of other warm-season tallgrasses to be greatest in late summer or fall and suggested the fungal symbiont might be parasitic at this time.…”
Section: Discussionsupporting
confidence: 86%
“…AM colonization of S. wrightii continued at a higher level in the summer ( July) at two sampling sites ( UP and UI), but then declined to the lowest levels in fall (September) when big sacaton shifted from vegetative growth to reproduction, and in December when hosts were dormant, or approaching dormancy. This pattern of change in fungal colonization is similar to that reported by Ebbers et al (1987) in their study of S. heterolepsis. Bentivenga & Hetrick (1992) found total colonization of other warm-season tallgrasses to be greatest in late summer or fall and suggested the fungal symbiont might be parasitic at this time.…”
Section: Discussionsupporting
confidence: 86%
“…Dickman et al (1984) reported a decrease in little bluestem colonization from May to September. However, in a study of prairie dropseed {Sporobolus heterolepis) on two sites there was no change in colonization during the growing season on one site, while colonization on the other increased from spring to fall (Ebbers et aL, 1987). In contrast, in this study, percent colonization did not vary significantly on the burned sites, although colonization levels always increased toward the end of the growing season.…”
Section: Discussioncontrasting
confidence: 86%
“…Similar peaks in VAM fungi spore counts were found within the root zone of crop plants in autumn (October) (Sulton & Baron, 1972) and in native sunfiower plants in fall (September) (Anderson & Liberta, 1987). However, Dickman et al (1984) reported, for several sites, peak spore counts in spring (May) which declined in the summer (July) and then increased slightly in autumn (September).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations